Overview and Tendencies of Augmented Reality Applications in Medicine - Santos, Bruna S. R.; Trevisan, Daniela (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Recently, augmented reality (AR) has received increasing attention, with the development of AR devices such as head-mounted displays, haptic devices, and AR glasses. Healthcare can be considered to be one of the most effective applications of AR. In this article, we describe a literature systematic mapping conducted to investigate the state-of-the-art AR technology in order to help doctors and future doctors in a wide range of applications and opportunities. The 160 studies that were ultimately collected were categorized into 3 representative topics: main goals of using AR in healthcare, the most used technologies, and how these studies were evaluated or measured. Finally, we reflected on the biggest challenges for future research and opportunities in using AR next years. At this point, improvements in tracking techniques and appropriate assessments of the tool in a clinician’s daily routine could be essential for identifying points that were not seen in controlled testing scenarios.